Climate-Smart Agriculture in Nepal: Champion technologies and their pathways for scaling up - Poudel, Bikash; Khanal, Ram Chandra; Bhatta, Kiran; Chaudhari, Pashupati; Khatri-Chhetri, Arun (Climate and Development Knowledge Network, 2017)
This policy brief synthesises key findings and recommendations for decision-making under uncertainty in the agriculture sector in Nepal. This brief highlights the methodologies used for selection of champion climate-smart agriculture (CSA) practices for different agro-ecological regions of Nepal and recommendations for scaling up the champion CSA technologies and practices in Nepal. Adaptation to climate change in the agricultural sector and allied sectors is a major current and future challenge for Nepal. The majority of the population is still dependent on highly climate-sensitive agriculture. In recent years, long drought spells during the monsoon season and increased temperatures and unseasonal heavy rains during winter have caused serious distress to agriculture-dependent communities in many locations. If the Sustainable Development Goals (SDGs) of ending poverty, achieving food security and promoting sustainable agriculture are to be realised, climate change adaptation interventions need to be implemented in earnest.